PENGARUH LKS DALAM PEMBELAJARAN PROBLEM BASED INSTRUCTION TERHADAP HASIL BELAJAR FISIKA SISWA KELAS XI SMA N 2 PARIAMAN - Diani Asyhari (Universitas Negeri Padang, 2013)
The purpose of this research is to know the influence of the using of LKS in learning Problem Based Instruction (PBI) towards the achievement of competence of grade IX students of SMAN 2 Pariaman. The types of this research is Quasi-eksperimental. The population of this research are all of the students of grade XI of SMAN 2 Pariaman. The taken of this sample is by Cluster Random Sampling, so that taken grade XI IPA 3 as experiment class, and grade XI IPA 2 as control class. The data of the research are the results of cognitive study, affective, and psikomotor. The results of research shows by using equality test of two averages, t test in cognitive and psikomotor and t’ test in affective, found that -t(1-1/2α)< th >t(1-1/2α). So, using LKS PBI give study result better than using LKS that is giving at school. Keywords : Worksheet, PBI, Physics, Learning Outcomes